Facial Rejuvenation: A Comparative Analysis of Platelet-Rich Plasma and Growth Factor Serums - Khattak, Arzu; Alsalmi, Dhoha Mohamed Ahmed; Kariem, Ashtar; Alshamsi, Fatima Abdalla; Alshamsi, Mahra Khalid; Alghamdi, Hind A; Roy, Daisy; Khan, Ramla Mehak; Bedwawi, Mariam Al; Azhar, Misbah Azhar (Indus Journal of Bioscience Research, 2024)
Background: Facial aging arises from intrinsic factors like collagen degradation and extrinsic factors such as UV exposure, leading to wrinkles, reduced elasticity, and pigmentation changes. Platelet-Rich Plasma (PRP) and Growth Factor Serums (GFS) are promising non-invasive treatments targeting these issues through distinct biological mechanisms. PRP promotes dermal regeneration via growth factors like PDGF and VEGF, while GFS enhances epidermal hydration through bioengineered proteins such as EGF and FGF. However, comparative analyses of their efficacy remain limited [1, 6, 9]. Objectives: To comprehensively compare PRP and GFS in facial rejuvenation, focusing on biological mechanisms, clinical efficacy, patient satisfaction, safety profiles, cost-effectiveness, and long-term outcomes. Methodology: A systematic review of 32 studies published between 2010 and 2024 was conducted, including randomized controlled trials (RCTs), cohort studies, and meta-analyses. Data were extracted from PubMed, Embase, and Web of Science databases using structured search terms. Statistical and meta-analytical methods were applied to synthesize findings [4, 8, 12]. Results: PRP significantly improved collagen density (18% increase, 95% CI: 12–24%) and skin elasticity (SMD = 1.12, 95% CI: 0.86–1.38, p < 0.001), with effects lasting up to 18 months. GFS was effective in improving epidermal hydration (SMD = 0.89, 95% CI: 0.61–1.17, p < 0.01) but required consistent use. PRP achieved higher patient satisfaction (8.5/10) compared to GFS (7.2/10). Combination therapies showed synergistic benefits [7, 9, 11]. Conclusion: PRP and GFS address distinct aspects of skin aging. PRP excels in deep dermal regeneration, while GFS provides maintenance-focused improvements. Combining both modalities offers promising outcomes but requires standardized protocols [6, 18].